Modeling QoS parameters of VoIP traffic with multifractal and Markov models - Toral-Cruz, Homero; Pathan, Al-Sakib Khan; Ramírez-Pacheco, Julio C. (Springer-Verlag, Berlin, Germany, 2011)
In this paper, we analyze the jitter and packet loss behavior of voice over Internet protocol (VoIP) traffic by means of networks measurements and simulations results. As result of these analyses, we provide a detailed characterization and accurate modeling of these Quality of Service (QoS) parameters. Our studies have revealed that VoIP jitter can be modeled by self-similar and multifractal models. We present a methodology for simulating packet loss. Besides, we found relationships between Hurst parameter (H) with packet loss rate (PLR).